Affiliation, Aggression, and Selectivity of Peer Relationships in Meadow and Prairie Voles - Lee, Nicole S.; Goodwin, Nastacia L.; Freitas, Katherine E.; Beery, Annaliese K. (Frontiers in Behavioral Neuroscience, 2019)
Relationships between adult peers are central to the structure of social groups. In some species, selective preferences for specific peers provide a foundation for consistent group composition. These preferences may be shaped by affiliation toward familiar individuals, and/or by aversion to unfamiliar individuals. We compared peer interactions in two vole species that form selective preferences for same-sex individuals but differ in mating system. Prairie voles (Microtus ochrogaster) form pair bonds with mates and may reside in family groups. Meadow voles (Microtus pennsylvanicus) are promiscuous breeders that form communal winter groups in the wild, and exhibit greater social behavior in short day lengths in the laboratory. We characterized affiliative, anxiety-like, and aggressive interactions with familiar and novel same-sex conspecifics in meadow and prairie voles housed in summer- or winter-like photoperiods. Species differences in affective behaviors were pronounced, with prairie voles exhibiting more aggressive behavior and less anxiety-like behavior relative to meadow voles. Meadow voles housed in short (vs. long) day lengths were more affiliative and more interactive with strangers; prosocial behavior was also facilitated by a history of social housing. Prairie voles exhibited partner preferences regardless of sex or day length, indicating that selective peer preferences are the norm in prairie voles. Prairie vole females formed preferences for new same-sex social partners following re-pairing; males were often aggressive upon re-pairing. These data suggest that preferences for familiar peers in prairie voles are maintained in part by aggression toward unfamiliar individuals, as in mate partnerships. In contrast, social tolerance is an important feature of meadow vole peer affiliation, demonstrated by low aggression toward unfamiliar conspecifics, and consistent with field data on winter tolerance.